The Effects CNG Injection Timing on Engine Performance and Emissions Of A Diesel Dual Fuel Engine - Moch. Aziz Kurniawan; Dori Yuvenda; Bambang Sudarmanta (IPTEK, LPPM, Institut Teknologi Sepuluh Nopember, 2019)
Sequential combustion process on diesel dual fuel engine with compressed natural gas (CNG) fuel was complex. The problems of diesel dual fuel with CNG gas are reduced thermal efficiency and resulting in high carbon monoxide (CO) and unburned hydrocarbon (HC) emissions. The right setting between combustion air, diesel pilot fuel, and CNG gas fuel can improvement the performance and emissions. The experiment was conducted with diesel fuel conventional and dual fuel mode with CNG fuel in a single cylinder, four strokes, constant speed (1500 rpm) diesel engine type diamond DI 800. Performance parameters such as thermal efficiency and specific fuel consumption (SFC), emissions such as CO, HC, and smoke density are determined at five starts of injection timing (SOI) CNG of 700CA, 900CA, 1100CA, 1300CA, dan 1500CA ATDC with ECU programmable of Vemstune software. The results indicated that retarded CNG injection timings improved engine performance and emissions diesel dual fuel. Start of CNG injection timing optimization at 1300CA ATDC with increased thermal efficiency 14,35% and decreased specific fuel consumption (SFC) 8,83 % . in addition, it decreased CO emissions 21,35%, HC emissions 17,93%, and PM emissions lower 34,98%. However, engine performance diesel dual fuel lower than a conventional diesel engine.